"A great stress among students" - mental health nurses' views of medication education: A qualitative descriptive study. (June 2019) - Goodwin, John; Kilty, Caroline; Harman, Mark; Horgan, Aine
Abstract: Background: Registered mental health nurses report dissatisfaction with the level of medication knowledge demonstrated by undergraduate nurses. However, little is known about which particular areas staff nurses are concerned about, and how they feel education can be enhanced in both academic and clinical settings. Objective: To investigate the views of staff nurses on the delivery of medication education to undergraduate mental health nurses. Design: A qualitative descriptive design was adopted. Methods: Two focus groups were held with registered nurses in two acute mental health facilities. Data were analysed using qualitative content analysis. Results: The first theme reports on the difficulties staff nurses observed with both undergraduate and newly qualified nurses around medication. It was noted that these individuals had difficulties interpreting medication charts/Kardexes, and were unable to provide medication-related education to service users. The second theme reports on strategies to enhance medication education, as recommended by participants. It was suggested that more practical education should be delivered in academic settings, with a focus on simulation and presentations from clinical staff. In the clinical settings, it was suggested that preceptors should provide education at less busy times on the ward. Conclusions: This study gives insight into areas in which education needs to be strengthened, in order to improve the medication knowledge of undergraduate and newly qualified nurses. Further research is needed to develop evidence-based strategies to enhance this education.